Algorithm implementation in MATLAB for root measurement - Ferrón-Carrillo, Francisca; Gómez-Cortés, Juan Carlos; Regalado-Sánchez, Julio; Urrestarazu, Miguel; Castellano, Nuria Novas (Computers and electronics in agriculture, 2020)
[Display omitted] •A better efficiency of root analysis was found with a non-invasive method.•MATLAB produced a smaller error when calculating volume conversion than Image J.•Root area was recorded with an error of less than 5% between the results obtained.•The application of the method in hydroponics could be extended in soil crops. Modern agriculture has a growing level of technification, through the incorporation of new technologies of great utility in other disciplines different from the agricultural sector. The use of remote sensing systems to monitor the physiological state of crops by observing the volume and appearance of the roots is another example of its application. These systems are based on the detection and recording of spectral variations of crops both in the range of visible radiation and within the electromagnetic spectrum in the infrared range. Thermography is a visual tool that has found applications in agriculture. The monitoring of water status through the observation of crop roots is essential to optimize the use of water in agriculture, as well as its development and final production. The efficiency of root growth in basil crops has been analysed in a chamber with controlled humidity and temperature. The aim of this work was to demonstrate a better efficiency of root analysis with a first non-invasive and environmentally friendly method, visually, using thermal imaging and digital processing in the evaluation of radical growth versus two other conventional methods: traditional standard analysis and invasive analysis with digital image treatment. The results also showed advantages in the use of thermographic images compared to the use of RGB images for roots smaller than 1 mm.